2024
DOI: 10.1039/d4cp00095a
|View full text |Cite
|
Sign up to set email alerts
|

UV-resonant magnetoplasmonic properties of chemically synthesized indium nanoparticles

Ririka Matsuda,
Hiroshi Yao

Abstract: In this article, magneto-optical (MO) properties of metallic indium (In0) nanoparticles, as one of the promising non-noble metals for UV plasmonics, are investigated using magnetic circular dichroism (MCD) spectroscopy. In0...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Fortunately, some recent studies on blue Nb-doped TiO 2 nanodots demonstrated a broad LSPR peak at 2500–3500 nm (or 4000–2857 cm –1 ), ,, so we here assume that the LSPR band has a Gaussian profile with E LSPR = 3333 cm –1 (= 3000 nm). We then simulated the MCD signature using a deconvoluted Gaussian profile as input (see the tail component 1 in Figure a), applied a simple blue/red-shift approximation, with one shifted to higher energy (+ℏω c /2) and the other shifted to lower energy (−ℏω c /2), and took the difference between them in accordance with the shape and intensity. ,, In simulating the spectra, additionally, dichroism (Δ A = (MCD/33) in degree unit) is normalized by both A max (absorbance at the LSPR maximum) and B (in tesla). A max could be obtained by the simultaneous simulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, some recent studies on blue Nb-doped TiO 2 nanodots demonstrated a broad LSPR peak at 2500–3500 nm (or 4000–2857 cm –1 ), ,, so we here assume that the LSPR band has a Gaussian profile with E LSPR = 3333 cm –1 (= 3000 nm). We then simulated the MCD signature using a deconvoluted Gaussian profile as input (see the tail component 1 in Figure a), applied a simple blue/red-shift approximation, with one shifted to higher energy (+ℏω c /2) and the other shifted to lower energy (−ℏω c /2), and took the difference between them in accordance with the shape and intensity. ,, In simulating the spectra, additionally, dichroism (Δ A = (MCD/33) in degree unit) is normalized by both A max (absorbance at the LSPR maximum) and B (in tesla). A max could be obtained by the simultaneous simulation.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclotron or shift frequency ω c is a function of the effective mass of electron (= m *) and expressed as eB / m *, where e denotes the electron charge; that is, ω 0 ± ω c /2 = ω 0 ± eB /(2 m *) . Therefore, the value of m * in the Nb-doped blue TiO 2 ( Nb-TD 120–4 ) can be estimated by deconvolution of the optical absorption and simultaneous MCD simulation based on the successful fitting of both spectra. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation